A Development of Think Pair Share Learning System Using Mobile Learning - พลคชา พิทักษ์; แซ่หลี สมคิด; สินธนะกุล กฤช (Journal of Roi Et Rajabhat University, 2016)
The purposes of this research were to develop and to find the quality of a think pair share learning system using mobile learning. The development process was the ADDIE Model instructional design framework. The sample in this research was 5 experts with following qualification: 1) associate professor; assistant professor or doctoral degree; and 2) graduated in technology and communication; computer education; information technology. The purposive sampling was used to select the sample of this study. The tools used for this research consisted of 1) Think pair share learning system using mobile learning; and 2) Questionnaires. The results showed that; the overall system quality was very high ( =4.60, S.D.=0.51). When consider each aspect, the convenience of use of the system ( =4.69, S.D.=0.47). The functional requirement test ( =4.66, S.D.=0.49). The security test ( =4.64, S.D.=0.49). The function speed of the system ( =4.60, S.D.=0.51) was very high. The results of the study were evaluated think pair share learning using mobile learning on all aspects was very high, this shows that the system is a quality learning system which can be used in teaching.